Taxonomic novelties and nomenclatural updates in Justicia (Acanthaceae) from the Brazilian Cerrado - Sartin, Rodolph Delfino; Silva, Fabio Araújo Da; Fernandes, Ulisses Gonçalves; Kameyama, Cíntia; Pirani, José Rubens (Phytotaxa, 2026)
Justicia s.l. is the most species-rich genus in Acanthaceae, comprising more than 700 species worldwide. During taxonomic studies of the genus in the state of Goiás, central Brazil, three new species—Justicia dissimulata, J. kalunga, and J. oreadica—are described. Regarding their distribution, J. dissimulata potentially extends to Mato Grosso, J. kalunga is endemic to Goiás, and J. oreadica also occurs in the Federal District. Detailed illustrations, photographic plates, distribution maps, and comments on morphological delimitation and conservation status are provided. In addition, two new nomenclatural combinations, lectotypifications, and the recognition of new synonymies are proposed. Data on geographic distribution, habitat, phenology, and diagnostic morphological characters are also presented.